Effect of Amniotic Membrane Suspension (AMS) and Amniotic Membrane Homogenate (AMH) on Human Corneal Epithelial Cell Viability, Migration and Proliferation In Vitro. (4th March 2017) - Wu, Ming-Feng; Stachon, Tanja; Langenbucher, Achim; Seitz, Berthold; Szentmáry, Nóra
ABSTRACT: Purpose : To analyze the effects of different concentrations of amniotic membrane suspension (AMS) or amniotic membrane homogenate (AMH) on human corneal epithelial cell (HCEC) viability, migration and proliferation. Methods : Amniotic membranes (AMs) of 13 placentas were prepared and stored at −80°C. For AMS preparation, following de-freezing, AM pieces were inserted in six-well plates and 5 ml Dulbecco's Modified Eagle's Medium (DMEM)/F12 (with 5% fetal bovine serum, FBS) per gram tissue was added for 96 h. After removal of the AM, the remaining supernatant was collected for experiments. For AMH preparation, following de-freezing, AMs were homogenized in liquid nitrogen and 5 ml DMEM/F12 (with 5% FBS) per gram tissue was added. Following centrifugation, the supernatant was collected for experiments. HCECs were expanded and incubated in DMEM/F12, 5% FBS supplemented by 15%, 30% or 100% AMS or 15% or 30% AMH. Viability was analyzed using Cell Proliferation Kit XTT, migration using wound healing assay and proliferation by the cell proliferation ELISA BrdU kit. Results : HCEC viability remained unchanged using 15% or 30% AMS ( p = 1.0 for both); however, it decreased significantly using 100% AMS ( p < 0.001) or 15% ( p = 0.041) or 30% AMH ( p < 0.001), compared to controls. Using 15% or 30% AMS, HCEC migration increased significantly ( p < 0.001 for both). Using 15% or 30% AMH ( p = 0.153; p = 0.083), HCEC migration remained unchanged and 100% AMS inhibited HCEC migration ( p < 0.001). Next, 15% and 30% AMS had no effect on HCEC proliferation ( p = 0.454 and p = 0.119), but 100% AMS ( p < 0.001) and 15% ( p = 0.002) and 30% AMH ( p = 0.001) inhibited HCEC proliferation significantly. Conclusion : With unchanged HCEC viability and proliferation and increased HCEC migration, 15% and 30% AMS application seems to be the most appropriate method to support epithelial healing.